2002
DOI: 10.1521/pedi.16.5.402.22122
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Dimensions and Facets of the Five-Factor Model in the Diagnosis of Cases of Personality Disorder

Abstract: Two national samples of psychologists (n = 92, n = 89) rated personality disorder cases using either the five factors (domains) or the 30 facets of the five-factor model (FFM) to examine reliability and clinical utility of the model when used as a diagnostic tool. The cases were prototypic and nonprototypic cases representing the three clusters of personality disorders in the DSM-IV. Although confidence was higher using the factors rather than the facets to rate the cases, interrater reliability was similar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 28 publications
4
55
0
Order By: Relevance
“…Use of dimensional diagnosis for personality pathology may be particularly challenging when there is comorbid Axis I pathology, which is typical of individuals presenting for treatment. In addition, whereas this study utilized the higher order dimensions of the models, future research might examine the lower order dimensions and traits, which may be more useful for clinical practice (i.e., Dyce & O'Connor, 1998;Livesley & Jang, 2000;Lynam & Widiger, 2001;Sprock, 2002;Widiger, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Use of dimensional diagnosis for personality pathology may be particularly challenging when there is comorbid Axis I pathology, which is typical of individuals presenting for treatment. In addition, whereas this study utilized the higher order dimensions of the models, future research might examine the lower order dimensions and traits, which may be more useful for clinical practice (i.e., Dyce & O'Connor, 1998;Livesley & Jang, 2000;Lynam & Widiger, 2001;Sprock, 2002;Widiger, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Average inter-rater reliability was good, ranging from .48 to .66. Samuel and Widiger 26 (see also Sprock 28 ) also demonstrated that practicing clinicians could also describe the personality disorders in terms of the FFM with fairly high inter-rater agreement, ranging from .64 to .78. Samuel and Widiger 26 also found extremely high agreement between the prototypes derived from practicing clinicians and those from experts in personality disorders 27 .…”
Section: Back-translation Task Used In Rottman Et Al25mentioning
confidence: 96%
“…Research studies examining relations between the DSM PDs and measures of normal-range personality, including the FFM, have revealed that the domains of normal and abnormal personality are largely overlapping (O'Connor 2002). More specifically, the DSM PDs can be characterized with the FFM conceptually-by both clinical researchers and practicing clinicians (Samuel & Widiger 2004, 2006Sprock 2002)-and empirically (O'Connor 2005, Saulsman & Page 2004.…”
Section: Personality Disorder Diagnosis and The Ffmmentioning
confidence: 99%
“…Lowerorder (facet-level) characterizations differentiate better among individuals with PD than do higher-order (domain-level) ones (Bagby et al 2005a, Morey et al 2002, Reynolds & Clark 2001. Moreover, practicing clinicians rated facets as more useful clinically than domain scores (Sprock 2002).…”
Section: Personality Disorder Diagnosis and The Ffmmentioning
confidence: 99%